Predictors for Prognosis in Patients With Nonfatal Pulmonary Embolism: A Registry-Based Cohort Study. (December 2018) - Bosevski, Marijan; Krstevski, Gorjan; Gjorgievski, Atanas; Mitevska, Irena; Kostovska, Elizabeta Srbinovska
The article's aim was to determine predictors for short- and long-term prognosis of patients with pulmonary embolism (PE). Cohort prospective study based on the National registry on venous thromboembolism. Eighty-four patients with PE, on age 60.3 + 12.5 years, were selected and followed up in a prospective study. Pulmonary embolism was confirmed by computed tomography angiography in all the patients, while deep venous thrombosis was confirmed by ultrasound in 21 patients. Study population was followed up for 6.7 months. Multivariate regression analysis was done where right ventricular (RV) diameter (mean 37.5 mm), systolic pulmonary artery pressure (68 ± 23 mm Hg) measured by echocardiography, d -dimer level at baseline 2654.5 ± 420.3 ng/mL, number of comorbidities (2.4 ± 0.7), and present symptoms (3.1 ± 0.9) entered the model. The model was age-adjusted.d -dimer level was revealed as a predictor for the length of hospitalization (β = .25, P = .05) and RV diameter as a factor for duration of anticoagulation (β = .29, P = .05). Our results imply that the baseline measurement of these parameters independently influence both the short-term and long-term prognosis of patients with nonfatal PE.